Respostas
respondido por:
0
Resposta:
. M(x, y) = M(- 2, - 2)
Explicação passo a passo:
.
. Pontos: A(3, - 2) e B(- 7, - 2)
.
. Ponto médio de AB: M(x, y), tal que:
.
. xM = (xA + xB) / 2 e yM = (yA + yB) / 2
. = (3 + (-7)) / 2 = (- 2 + (-2)) / 2
. = - 4 / 2 = - 4 / 2
. = - 2 = - 2
.
(Espero ter colaborado)
.
joaosilvz15:
consegue me mandar foto?
respondido por:
0
P(x , y) = A(x , y) e B(x , y)
xM = (xA + xB)/2
xM = (3 + (- 7))/2
xM = (3 - 7)/2
xM = - 4/2
xM = - 2
yM = (yA + yB)/2
yM = (- 2 + (- 2))/2
yM = (- 2 - 2)/2
yM = - 4/2
yM = - 2
M(x , y) = M(- 2 , - 2)
atte. yrz
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás